2018
DOI: 10.1519/jsc.0000000000002348
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Filtration Rate Is Unchanged by Ultramarathon

Abstract: In contrast to the majority of previous studies, we did not observe any decrease in the kidney function during an ultramarathon. In this study the creatinine clearance, which is the best routine laboratory method to determine glomerular filtration rate was used. There is no evidence that long running is harmful for kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
12
0
1
Order By: Relevance
“…This work demonstrates that, depending on the methodology used, AKI criteria was met by 21%‐63% of the subjects following the ultramarathon. This is consistent with prior work demonstrating a 25%‐80% incidence of the criteria being met during ultramarathons of various distances 11,14,30,31 . The implications of such high incidents of AKI criteria being met are not clear, but the current belief is that there is no reason for concern about long‐term harm to the kidneys in ultramarathon runners 31,32 .…”
Section: Discussionsupporting
confidence: 87%
“…This work demonstrates that, depending on the methodology used, AKI criteria was met by 21%‐63% of the subjects following the ultramarathon. This is consistent with prior work demonstrating a 25%‐80% incidence of the criteria being met during ultramarathons of various distances 11,14,30,31 . The implications of such high incidents of AKI criteria being met are not clear, but the current belief is that there is no reason for concern about long‐term harm to the kidneys in ultramarathon runners 31,32 .…”
Section: Discussionsupporting
confidence: 87%
“…Besides, severe cases of AKI in non-runners may require dialysis and are especially vulnerable to worse long-term renal outcomes [ 154 ]. Occasionally, AKI is detected in combination with rhabdomyolysis that may lead to a more complex condition in UER [ 144 , 155 157 ]. It is currently unknown if severe renal dysfunction in UER, or repetitive renal insults that meet the criteria of AKI, lead to an accelerated progression of long-term renal issues in UER [ 134 , 145 , 147 , 158 ].…”
Section: Long-term Health Implications: Key Aspects By Organ Systemmentioning
confidence: 99%
“…Therefore, whether ultra-marathon running by itself increases the risk of acute kidney injury need to be clarified. Some recent studies have shown an unchanged glomerular filtration rate by ultramarathon (Wołyniec et al, 2018), or no evidence that prior acute kidney injury caused greater renal dysfunction from a subsequent exercise stimulus (Hoffman and Weiss, 2016). We wanted to test the hypothesis that in common conditions (no use of NSAIDs and no major risk of dehydration), ultra-distance race has no supplemental short-term impact on acute kidney function.…”
Section: Introductionmentioning
confidence: 99%